2016
DOI: 10.2298/abs150911032k
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Douglas fir monoculture on stand characteristics in a zone of Montane beech forest

Abstract: The right choice of tree species to form forest cultures is of paramount importance to the preservation of the diversity, fertility and ecological stability of forest ecosystems. To that end, we examined the effect of a 40-year-long cultivation of Douglas fir (Pseudotsuga menziesii (Mirb) Franco) on the floristic composition, characteristics of the forest floor, physical and chemical properties of the soil and the intensity of organic matter decomposition in a beech forest in western Serbia (Mt. Maljen). It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The study area lying within the forty-year-old silvicultural system of Douglas fir and the control area within the autochthonous beech forest are characterised by the same ecological conditions, i.e. western exposure, a 2-5 ° slope, and the same soil types, formed on the same geological substrate (diabase), (WRB, Cambisol, dystric 2006;Kostić et al, 2016;Pavlović et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study area lying within the forty-year-old silvicultural system of Douglas fir and the control area within the autochthonous beech forest are characterised by the same ecological conditions, i.e. western exposure, a 2-5 ° slope, and the same soil types, formed on the same geological substrate (diabase), (WRB, Cambisol, dystric 2006;Kostić et al, 2016;Pavlović et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Even though these processes are related to moisture, temperature, aeration and the physical and chemical properties of the soils, as well as soil macrofauna activity, leaching by water and humus stabilisation (organomineral complexes and aggregates), the primary factor in these processes is the amount and quality of litter from woody species. For this reason, tree species substitution affects the quality and quantity of annual organic matter stock, as well as the decomposition rate, and can thus have a considerable impact on the modification of the physical and chemical characteristics of soil and on the processes in the soil (Pavlović et al, 1998;Albers et al, 2004;Moukoumi et al, 2006;Kostić et al, 2012Kostić et al, , 2016. Hence, the amount of organic matter and its dynamics have become a focus of research (Augusto et al, 2002;Moukoumi et al, 2006;Bonifacio et al, 2008;Kostić et al, 2012Kostić et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C/N ratio in the soil surface layer in spruce plantations was in the range from 13.9 to 15.4, as opposed to 11.1 to 19.7 in natural stands. With increasing depth, the C/N ratio is reduced (Kostić et al 2016). In the present study, the C/N ratio at depths of 10-20 cm in the spruce plantations ranged from 11.1 to 14.9, as opposed to 9.8 to 17.5 in natural stands.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…Research has shown that certain species, tipically when planted in a monoculture, have varying impacts on soil (Klimo 2000). The specificity of such impacts is associated with the nature of the tree species, in terms of the quality and quantity of the organic matter participating in humus production, nutrient cycling, fertility maintainance and ecological stability of the forest ecosystem (Augusto et al 2002, Mareschal et al 2010, Kostić et al 2016), leading to a modification of local microclimate and pedoclimate. Furthermore, the specific influences of vegetation on soil are associated with the macroclimatic conditions which will determine the production of organic matter and the dynamics of its humification and mineralisation (Berg & Mc-Claugherty 2008).…”
Section: Introductionmentioning
confidence: 99%